Overgeneral autobiographical memory in depressed adolescents with, versus without, a reported history of trauma. - Kuyken, W; Howell, R; Dalgleish, T (2006)
Autobiographical memory retrieval is fundamental to the developing self-concept in adolescence, to emotion regulation, and to social problem solving and has been shown to be compromised in adolescents diagnosed with depression (R. J. Park, I. M. Goodyer, and J. D. Teasdale, 2002). The authors of the present study assessed autobiographical memory overgenerality in a sample of depressed adolescent participants with, versus without, a reported history of trauma and never-depressed control participants by using an emotion word-cueing paradigm. The authors' analyses showed for the first time that adolescents with major depression and with no reported history of trauma exhibited an overgeneral memory bias. They also revealed that depressed adolescents who reported a history of trauma retrieved fewer overgeneral memories than did depressed adolescents who reported no history of trauma. Among depressed adolescents who reported a history of trauma, more severe posttraumatic stress symptoms were associated with less overgenerality. Possible accounts of these findings are suggested.